HEALTH EVALUATION OF PT BANK SYARIAH INDONESIA TBK (BSI) THROUGH THE RBBR METHOD: A REVIEW OF THE PERIOD 2014-2023 - Nurhayati, Anggita; Suwantri, Kristiana; Nengtias , Defia Oktaviana (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the financial health of PT Bank Syariah Indonesia Tbk (BSI) from 2014 to 2023 using the Risk-Based Bank Rating (RBBR) method. The research focuses on evaluating key financial indicators, including Non-Performing Financing (NPF), Good Corporate Governance (GCG), Return on Assets (ROA), and Capital Adequacy Ratio (CAR), to assess BSI's performance, challenges, and risk management strategies. Method: The analysis employs the RBBR method, as outlined in OJK Circular Letter No.14/SEOJK.03/2017, to evaluate BSI's financial health. This method assesses four main aspects: Risk Profile (measured using NPF), Good Corporate Governance (GCG), Earnings (measured using ROA), and Capital (measured using CAR). Data was collected from financial reports, regulatory publications, and relevant literature, and was processed to determine BSI's financial health score. Results: The findings indicate that BSI maintained a stable financial health score, fluctuating between the "Healthy" and "Very Healthy" categories. The NPF ratio decreased from 3.21% in 2019 to 2.08% in 2023, demonstrating effective credit risk management. The highest financial health score was achieved in 2021 at 95%, attributed to revenue growth and efficient cost management. However, challenges emerged in 2022 due to a data leak incident that impacted the bank’s reputation, leading to a decline in financial health. Additionally, the withdrawal of Rp 13-15 trillion by the Muhammadiyah Central Executive in 2024 raised concerns about liquidity risk. Novelty: This study provides a comprehensive assessment of BSI’s financial health over a decade, highlighting both its resilience and vulnerabilities. Unlike previous studies, it integrates cybersecurity risks and liquidity challenges into the financial health analysis, emphasizing the importance of risk diversification and investment in data security for long-term sustainability.